Role for Maternal Asthma in Severe Human Metapneumovirus Lung Disease Susceptibility in Children. (22nd January 2020) - Libster, Romina; Esteban, Ignacio; Bianchi, Alejandra; Alva Grimaldi, Luciano; Dueñas, Karina; Sancillo, Andrea; Rodriguez, Andrea; Ferrero, Fernando; Stein, Katherine; Acosta, Patricio L; Ferolla, Fausto M; Bergel, Eduardo; et al.
Abstract: Background: Severity of human metapneumovirus (hMPV) lower respiratory illness (LRTI) is considered similar to that observed for respiratory syncytial virus (RSV). However, differences in severity between these pathogens have been noted, suggesting the degree of illness may vary in different populations. Moreover, a potential association between hMPV and asthma also suggests that hMPV may preferentially affect asthmatic subjects. Methods: In a population-based surveillance study in children aged <2 years admitted for severe LRTI in Argentina, nasopharyngeal aspirates were tested by RT-PCR for hMPV, RSV, influenza A, and human rhinovirus. Results: Of 3947 children, 383 (10%) were infected with hMPV. The hospitalization rate for hMPV LRTI was 2.26 per 1000 children (95% confidence interval [CI], 2.04–2.49). Thirty-nine (10.2%) patients infected with hMPV experienced life-threatening disease (LTD; 0.23 per 1000 children; 95% CI, .16–.31/1000), and 2 died (mortality rate 0.024 per 1000; 95% CI, .003–.086). In hMPV-infected children birth to an asthmatic mother was an increased risk for LTD (odds ratio, 4.72; 95% CI, 1.39–16.01). We observed a specific interaction between maternal asthma and hMPV infection affecting risk for LTD. Conclusions: Maternal asthma increases the risk for LTD in children <2 years old hospitalized for severe hMPV LRTI. Abstract : In a population-based surveillance study in children aged <2 years admitted for severe lower respiratory tract illness in Argentina including more than 3900 patients, maternal asthma was associated with higher risk for life-threatening disease in human metapneumovirus infections.